Ancient crop beats salt - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Amaranth, an ancient cereal plant from South America, is making a comeback. Researchers have found that the plant tolerates saline soils and produces very nutritious food from land that has been abandoned to salt. Millions of hectares of farmland...